1998
DOI: 10.1086/300536
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar Disks in the Orion Nebula Cluster

Abstract: We combine our previous optical spectroscopic and photometric analysis of D1600 stars located in the Orion Nebula Cluster (ONC) with our own and published near-infrared photometric surveys of the region in order to investigate the evidence for and properties of circumstellar disks. We use the nearinfrared continuum excess as our primary disk diagnostic, although we also study sources with Ca II triplet emission and those designated as "" proplyds.ÏÏ The measured near-infrared excess is inÑuenced by (1) the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
289
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(308 citation statements)
references
References 51 publications
15
289
3
1
Order By: Relevance
“…The COUP tables list the color excess Á(I À K ) as determined by Hillenbrand et al (1998). This quantity represents the color excess relative to the expected photospheric colors for the star's spectral type after correction for reddening due to extinction and has been shown to be a useful tracer of circumstellar material (see discussion in Hillenbrand et al 1998). However, the Á(I À K ) excess is not optimal for detecting circumstellar material, since the K-band excess traces only the hottest dust in the innermost regions near the central star; it has been shown (e.g., Haisch et al 2001) that many stars with circumstellar material show significant excess emission only at longer wavelengths.…”
Section: X-ray Activity and Infrared Excess (=Inner Disk Tracer)mentioning
confidence: 99%
“…The COUP tables list the color excess Á(I À K ) as determined by Hillenbrand et al (1998). This quantity represents the color excess relative to the expected photospheric colors for the star's spectral type after correction for reddening due to extinction and has been shown to be a useful tracer of circumstellar material (see discussion in Hillenbrand et al 1998). However, the Á(I À K ) excess is not optimal for detecting circumstellar material, since the K-band excess traces only the hottest dust in the innermost regions near the central star; it has been shown (e.g., Haisch et al 2001) that many stars with circumstellar material show significant excess emission only at longer wavelengths.…”
Section: X-ray Activity and Infrared Excess (=Inner Disk Tracer)mentioning
confidence: 99%
“…The ONC data we used have been kindly provided by Keivan Stassun, who has widely worked on the rotational properties of the ONC (Stassun et al 1999(Stassun et al , 2004. The data consist of rotation periods (Stassun et al 1999 andHerbst et al 2002), effective temperatures and luminosities (Hillenbrand 1997), and infrared excesses, Δ[I − K] (Hillenbrand et al 1998). …”
Section: Onc Starsmentioning
confidence: 99%
“…They found a similar positive correlation between L Hα , Hα luminosity, and rotation period among the ctts. By using near-infrared excesses to identify disk candidates in the ONC, Hillenbrand et al (1998) concluded that this disk indicator misses about 30% of disks that can be detected at longer wavelengths. Then, in the attempt to use a more reliable disk indicator, Cieza & Baliber (2007) used data from the Spitzer Space Telescope in the IRAC band passes to test the star-disk interaction paradigm in NGC 2264 and the ONC.…”
Section: Introductionmentioning
confidence: 99%
“…For the systems θ 1 Ori A and θ 1 Ori C we use the photometric data compiled by Hillenbrand et al (1998). For θ 1 Ori B we use data in the 2MASS catalog, which we assume here to represent the combined fluxes of the components 3 B1, B2, and B3.…”
Section: Near-infrared Magnitudes Of the Components And Stellar Mass mentioning
confidence: 99%